Deciphering the causality of gut microbiota, circulating metabolites and heart failure: a mediation mendelian - Guan, Xueqing; Sun, Chaonan; Su, Jianyao; Sun, Zhijun; Cheng, Cheng (Frontiers in Pharmacology, 2025)
BackgroundGrowing evidence suggesting a connection between the gut microbiome, plasma metabolites, and the development of heart failure (HF). However, the causality of this relationship remains to be fully elucidated.MethodsUtilizing summary statistics from extensive genome-wide association studies (GWAS), we investigated the interplay among the gut microbiome, 1,400 plasma metabolites and heart failure. We conducted bidirectional Mendelian randomization (MR) analyses and MR mediation analysis to discern the causality within these relationships. The inverse variance-weighted (IVW) method served as our primary analytical approach, supported by various MR methods and sensitivity analyses.ResultsWe revealed casual relationships between nine microbial groups/pathways and heart failure. Additionally, 15 metabolites exhibited casual links with HF, with eight exerting protective effects. Through two-step MR analysis we also identified the metabolite, Campesterol, mediated the increasing risk from gut microbiota to HF and a metabolite ratio played the converse role.ConclusionThis investigation has provided robust evidence supporting the causal links between the gut microbiome, plasma metabolites, and heart failure. The findings enhance our comprehension of the role of circulating metabolites and offer significant insights for future etiological research and therapeutic development in heart failure.